2020
DOI: 10.3389/fonc.2020.602378
|View full text |Cite
|
Sign up to set email alerts
|

The Epigenetics of Glioma Stem Cells: A Brief Overview

Abstract: Glioma stem cells (GSCs) are crucial in the formation, perpetuation and recurrence of glioblastomas (GBs) due to their self-renewal and proliferation properties. Although GSCs share cellular and molecular characteristics with neural stem cells (NSCs), GSCs show unique transcriptional and epigenetic features that may explain their relevant role in GB and may constitute druggable targets for novel therapeutic approaches. In this review, we will summarize the most important findings in GSCs concerning epigenetic-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 87 publications
0
11
0
Order By: Relevance
“…In addition to the lack of consistent mutations affecting the histone H3 genes in TCGA database ( Table S4 ), we should consider in the light of our results that the induction of multiple canonical histone H3 genes in GB impose that rare mutations may only affect a small fraction of the total H3.1/H3.2 proteins. In contrast, mutations in the H3-3A gene are highly relevant in pediatric GB but they have a dominant-negative effect, while the reduction of the protein levels in adult H3-3A wild-type GB indicated a loss of function [ 23 , 51 ]; in the few adult cases with the mutated gene [ 52 ], it will be interesting to elucidate whether both mechanisms of H3.3 dysfunction coexist. Therefore, the impact of such variations should be clarified.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the lack of consistent mutations affecting the histone H3 genes in TCGA database ( Table S4 ), we should consider in the light of our results that the induction of multiple canonical histone H3 genes in GB impose that rare mutations may only affect a small fraction of the total H3.1/H3.2 proteins. In contrast, mutations in the H3-3A gene are highly relevant in pediatric GB but they have a dominant-negative effect, while the reduction of the protein levels in adult H3-3A wild-type GB indicated a loss of function [ 23 , 51 ]; in the few adult cases with the mutated gene [ 52 ], it will be interesting to elucidate whether both mechanisms of H3.3 dysfunction coexist. Therefore, the impact of such variations should be clarified.…”
Section: Discussionmentioning
confidence: 99%
“…The methylome of tumors has been integrated in most heterogeneity papers using high-throughput methods, especially for temporal heterogeneity studies. DNA methylation has also advanced the knowledge in intra-tumor spatial heterogeneity, especially in the characterization of CSCs and inflammatory cells [ 78 , 79 , 80 , 81 ]. Notably, differences in DNA methylation between tumor areas as close as 5 mm apart were observed, both in IDH mutant and IDH wild-type gliomas [ 64 ].…”
Section: Reviewmentioning
confidence: 99%
“…Overexpression of EZH2 in HGGs is associated with worse OS. This gene is part of the polycomb repressive complexes involved in the epigenetic modulation of GSCs, the most studied epigenetic modulators in GSCs, and is therefore a potential therapeutic target [ 80 ].…”
Section: Reviewmentioning
confidence: 99%
“…One of the major reasons for poor prognosis is glioma stem cells (GSCs) [3]. GSCs are characterized by high expression of the stem cell markers CD133, Nestin and Sox2 and extensive self-renewal and multilineage differentiation potentials [3][4][5]. Recent studies found that the initiation, progression, metastasis and recurrence of gliomas were mainly driven by GSCs [6][7][8].…”
Section: Introductionmentioning
confidence: 99%